Demystifying three species of Ctenidae (Arachnida: Araneae) described by Embrik Strand. Part I, Ecuador - Dupérré, Nadine (Zootaxa, 2014)
Ecuador is considered one of the most biodiverse countries in the world (Mittermeier et al. 1997), yet its spider fauna is unknown and understudied. Only 709 species distributed in 43 families are known to occur in Ecuador (Platnick 2013), whereas in Canada, a country much less biodiverse, the spider fauna is composed of 1405 spider species distributed in 43 families (Paquin et al. 2010). It seems reasonable to assume that a large part of the Ecuadorian spider fauna is still undiscovered. Furthermore, some groups are badly in need of revision, many species are known only from the type specimens, old descriptions and in some cases no illustrations were provided by the author making it difficult to recognise these species. In 1909, Embrik Strand described 17 new species of Ctenus Walckenaer, 1805 from South America (Strand 1909); seven of these species (three from Ecuador and four from Brazil) have never been illustrated or included in any recent taxonomic work. Even though Strand’s descriptions are quite elaborate, he did not provide any illustrations, thus making the identification of his species difficult. This paper is the first of two papers on Embrik Strand’s mysterious Ctenus species. The first part includes redescriptions and illustrations for the first time of the three Ecuadorian species: Ctenus datus Strand, 1909, C. inazensis Strand, 1909 and C. satanas Strand, 1909. This is the first step toward a comprehensive study of the family Ctenidae in Ecuador. The second part will include the redescriptions and illustrations for the first time of the four Brazilian species.